Financial Performance of Village-Owned Enterprises (VOEs): Case in Blitar Regency, East Java, Indonesia - Sari, Yuni Purwita; Putra, Fadilah; Sujarwoto, Sujarwoto (JPAS (Journal of Public Administration Studies), 2020)
Villages have many assets and potentials. Through Village-Owned Enterprises (VOEs), business entities owned by villages, the village assets, and potentials could be managed well for the greatest welfare of the village community. As public enterprises, VOEs are expected to play an important role in the mobilization of resources and they can do so if they are financially viable. Therefore, financial performance is a vital element for Village-Owned Enterprises (VOEs) sustainability. Using a multi-method design, this research aims to examine the growth of financial performance of VOEs in Blitar Regency from 2015 to 2019 and to explore factors that affect the financial performance of VOEs in Blitar Regency from 2015 to 2019. The results discovered that, in general, the financial performance of VOEs in Blitar Regency did not show any significant growth. Out of 85 observed VOEs, 74 of them did not go up from their previous level. However, there are VOEs whose financial performance is increase and decrease, which are five and six VOEs respectively. In addition, human resources, support from the Village Government, and VOE's ability to see business opportunities that exist in accordance with community needs and the potential of the village become the factors that affect the financial performance of Village-Owned Enterprises (VOEs). These factors should be considerations for policymaker and other stakeholders in setting appropriate programs or activities intended to enhance the development of VOEs, which will eventually, contributes to the village development.